Photometric, Spectroscopic, and Orbital Period Study of Three Early-type Semi-detached Systems: XZ Aql, UX Her, and AT Peg - Zola, S.; Baştürk, Ö.; Liakos, A.; Gazeas, K.; Şenavcı, H. V.; Nelson, R. H.; Özavcı, İ.; Zakrzewski, B.; Yılmaz, M. (2016)
In this paper, we present a combined photometric, spectroscopic, and orbital period study of three early-type eclipsing binary systems: XZ Aql, UX Her, and AT Peg. As a result, we have derived the absolute parameters of their components and, on that basis, we discuss their evolutionary states. Furthermore, we compare their parameters with those of other binary systems and with theoretical models. An analysis of all available up-to-date times of minima indicated that all three systems studied here show cyclic orbital changes; their origin is discussed in detail. Finally, we performed a frequency analysis for possible pulsational behavior, and as a result we suggest that XZ Aql hosts a δ Scuti component.
Keywords: Astrophysics - Solar and Stellar Astrophysics; AT Peg; binaries: eclipsing; stars: individual: XZ Aql; UX Her